Respuesta :
3x^4 – 18x^3 + 9x^2 –54x = 3x(x^2 + 3)(x - 6)
A = 3
B = 3
C = -6
The value of C is -6
A = 3
B = 3
C = -6
The value of C is -6
Answer: C=-6
Step-by-step explanation:
Given polynomial = [tex]3x^4-18x^3+9x^2-54x[/tex]
To factorize it , make pairs of terms and take greatest common factor out.
[tex]3x^3(x-6)+9x(x-6)\\=(x-6)(3x^3+9x)\\=(x-6)3x(x^2+3)\ or\ 3x(x^2+3)(x-6)[/tex]
On comparing corresponding terms of above factorized polynomial with [tex]Ax(x^2+B)(x+C)[/tex], we get
A=3 , B=3 and C=-6
hence, the value of C=-6